Low Temperature Synthesis and Characterization of Carbon Nanospheres from Saccharides - Kour, Rajpal (My University, 2017)
Nanostructures have sizes that lie between macroscopic and molecular structures. Carbon nanostructures attract large attention due to their attractive properties which can be modified. They find applications in diverse fields such as electrodes, sensors, catalyst support etc. Among these structures, carbon nanospheres (CNSs) are of great interest in scientific research due of their properties such as good electrical conductivity, high surface area, uniformity and thermal stability. They have been used in many applications such as Li-ion batteries, material reinforcement, fuel cells etc. In the present study the mono-dispersed carbon nanospheres were synthesized by hydrothermal process using various saccharide solutions – sucrose, glucose, and xylose. The saccharide solution in required concentration was sealed in a steel autoclave and heated at 180 °C for the prescribed time. The as-synthesized CNSs were characterized using X-Ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, Scanning electron microscope (SEM), Transmission electron microscope (TEM), UV-Visible spectroscopy, Thermo-gravimetry (TG) etc. for their structural, optical, thermal and other important properties. The size of the CNSs decreases with the saccharide solution concentration with smaller concentrations having more drastic effect. The CNSs produced from the present method typically have an average size in the range of 1500 – 15nm having smooth surfaces. Xylose gives the smallest CNSs. The CNSs were amorphous in nature. Samples show direct band gap which changes with the size of CNSs. This makes the synthesized samples viable for the photo catalytic applications in UV as well as visible region. The application of the synthesized CNSs as photo catalyst for organic waste degradation has been confirmed by degradation of methylene blue (MB) dye in the presence of UV and visible light. The degradation efficiency is more in visible light.
Masters Thesis
Keywords: Carbon Nanospheres; Sucrose; Hydrothermal Method; Saccharides; Photo catalysis